2012
DOI: 10.1016/j.jcrs.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Management of post-keratoplasty astigmatism

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
78
0
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 106 publications
(111 reference statements)
1
78
0
9
Order By: Relevance
“…This includes donor and recipient factors such as trephination, graft-host size disparity, wound healing and apposition, suturing technique, and suture material. 1 Different techniques are described to secure the grafthost junction. This includes double or single running sutures, interrupted sutures, and combined running and interrupted sutures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This includes donor and recipient factors such as trephination, graft-host size disparity, wound healing and apposition, suturing technique, and suture material. 1 Different techniques are described to secure the grafthost junction. This includes double or single running sutures, interrupted sutures, and combined running and interrupted sutures.…”
Section: Discussionmentioning
confidence: 99%
“…This can be extended to three or four sutures in steep semimeridians. 1,2,12 The rationale for this is that the effect of suture removal on the astigmatism is not instant both in terms of magnitude and vector, and a reassessment for residual astigmatism and axis was therefore undertaken between 3 and 6 weeks after removal of one pair (or four Figure 2 Refractive astigmatism before and after suture removal (dioptres), plotted as an astigmatic vector for each eye.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5] In recent studies, mean postoperative topographic astigmatism exceeding 6 diopters (D) has been reported in patients undergone PK. 6,7 Factors influencing the amount of astigmatism include the severity of underlying disorder (eg keratoconus), oval or eccentric trephination, graft size, donor recipient disparity, corneal thickness mismatch between donor and the recipient, a poor suturing technique and time of suture removal or adjustment.…”
mentioning
confidence: 99%